Doctors, Patients, and Society : Power and Authority in Medical Care - Larsen, Donald E. (Book collections on Project MUSE., 2006)
This book is a collection of papers presented at an interdisciplinary workshop at the Calgary Institute for the Humanities in May 1980. The three broad issues covered are: the physician-patient relationship, the allocation of responsibility among doctors and nurses, and the political and social framework of the health care system. The first set of essays is concerned with the moral and legal aspects of the physician-patient relationship. The link between knowledge and power is examined as well as the moral dilemmas posed by medical technology. These initial essays would alone justify this publ.